Epstein-Barr viral latent and early antigen serology in nasopharyngeal carcinoma - Tan, Timothy Ter Ming. (2008)
Nasopharyngeal carcinoma (NPC) is cancer of the nasopharynx in humans. It is an insidious and often rapidly fatal disease that is rare worldwide, but is very common among the Chinese from southern China and south-east Asia. It is difficult to detect since, in its early stages, patients are asymptomatic. However, NPC detected in its early stages is highly curable through radiation therapy. Clinically, it can be detected by an experienced medical practitioner using fibreoptic endoscopy, computer-assisted tomography or through serological tests. Serological testing detects the presence of specific antibodies to the Epstein-Barr virus, which is a crucial aetiological factor in the pathogenesis of the disease. Current methods include detection by indirect immunofluorescence assay which is laborious, subjective and requires highly-trained personnel, and enzyme-linked immunosorbent assay (ELISA), which can be easily performed by any hospital laboratory.